Research on the applicability of an exercise rehabilitation app aiming to improve the mental and physical health of breast cancer patients in the post-operative period - Zhu, Jiaxin; Niu, Hu; Lu, Dianjie; Li, Yuqi; Ding, Meng (Frontiers in Psychology, 2023)
Breast cancer is one of the most common malignant cancers in women, seriously endangering the physical and mental health of patients. In this study, we developed an app for breast cancer patients undergoing radiotherapy or chemotherapy with a focus on exercise interventions, supplemented by nutritional and psychological interventions, to verify the applicability of the app for these patients and its impact on their quality of life, sleep, and psychological state. We also investigated the patients' experience and perceptions of the app.